Light in architecture : the intangible material - Valero Ramos, Elisa (RIBA Publishing, 2015)
Part 1: The role of light in architecture -- Light and perception -- Light and geography -- Light as an instrument for abstraction -- Part 2: Working with light in architecture -- Natural light: bringing the outside, inside -- Filtered light: creating atmosphere -- Focused light: shadowplay -- Part 3: Light in architecture from past to present -- Light and architectural heritage -- Artificial light: the great invention -- Light today: from real to right.